2011
DOI: 10.1002/ijc.27343
|View full text |Cite
|
Sign up to set email alerts
|

Cryptotanshinone down‐regulates androgen receptor signaling by modulating lysine‐specific demethylase 1 function

Abstract: Development and progression of prostate cancer are intimately associated with androgen receptor (AR) signaling. The emergence of hormone-refractory prostate cancer and consequent failure of conventional androgen deprivation therapies make it necessary to bypass hormonal resistance by targeting the same signaling pathway at new intervention points. In our study, we showed that cryptotanshinone inhibited the growth of AR-positive prostate cancer cells, suggesting that cryptotanshinone affected AR function. Crypt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 48 publications
2
36
0
Order By: Relevance
“…Because AR co-regulators can determine specific AR targets in different types of cells (43), regulation of AR co-regulator interaction may also change the gene expression profile regarding the metastasis-related genes. A previous study showed that CTS can reverse the demethylation process mediated by LSD1 and inhibit AR transactivation at the epigenetic level (28). It would be interesting to identify the potential regulation of PCa metastasis abilities via epigenetic markers.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Because AR co-regulators can determine specific AR targets in different types of cells (43), regulation of AR co-regulator interaction may also change the gene expression profile regarding the metastasis-related genes. A previous study showed that CTS can reverse the demethylation process mediated by LSD1 and inhibit AR transactivation at the epigenetic level (28). It would be interesting to identify the potential regulation of PCa metastasis abilities via epigenetic markers.…”
Section: Discussionmentioning
confidence: 98%
“…Unlike the currently used anti-androgens that reduce or prevent androgen binding to AR, the newly developed anti-AR compound, ASC-J9, has the unique capability to degrade AR protein in selective cells. On the other hand, CTS also could suppress the AR activity by inhibition of N-terminal and C-terminal interaction or change the histone methylation pattern to reduce the AR transcriptional activity (12,28).…”
Section: Anti-androgen-induced Pca Invasion Involved the Activation Omentioning
confidence: 99%
“…Recently, CPT was reported to inhibit the androgen receptor activity and suppress prostate cancer growth in androgen-dependent manner, but the reason for that is not due to the direct bind to androgen receptor and is attributed to its functional inhibition of LSD1-mediated demethylation of H3K9. 19,20 Thanshinone I has been reported to induce apoptosis of breast cancer cells, 27 so it is possible that Thanshinone I also could inhibit ER transcriptional activity due to the similarity of the chemical structures of Thanshinone I and CPT. However, we found that anshinones I less effectively inhibited E2-induced transcriptional activity and expression of the ER target gene (pS2, and Cat D) in the presence of E2, compared with CPT, which is consistent with the same inhibitory effect of anshinones I on ERpositive as well as ER-negative cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17] Recently, CPT has also been reported to have obvious antitumor activity in a variety of cancer cells, including prostate carcinoma, hepatocarcinoma, rhabdomyosarcoma and melanoma cells. [18][19][20][21][22][23] In breast carcinoma cells, CPT has been shown to inhibit MCF7 cell proliferation by suppressing mTOR mediated CyclinD1 expression and Rb phosphorylation that lead to MCF7 cell apoptosis by inducing stress in the endoplasmic reticulum (ER). 24,25 However, it is not known whether CPT has any effects on estrogen-stimulated ER signaling and estrogen /ER mediated cancer cell growth.…”
Section: Introductionmentioning
confidence: 99%
“…LSD1 is frequently overexpressed in lung cancer (5,6), breast cancer (7), prostate cancer (8,9), and liver cancer (10). Importantly, overexpression of LSD1 promotes the growth and invasion of various types of cancer cells, and contributes to human carcinogenesis by regulating the expression of genes involved in various chromatin-modifying pathways (6).…”
Section: Introductionmentioning
confidence: 99%